A New model for the Calculation of Thermodynamic Functions of Simple Salts in Aqueous Solutions - Abdel-Halim, H.M. (Asian Journal of Chemistry, 2010)
Thermodynamic functions for simple salts in aqueous solutions have been calculated using a simple model based on the Born theory. A structural treatment of ion-solvent interactions has been considered. It takes into consideration ion-dipole, ion-quadrupole and ion-induced-dipole interactions as well as the Born-type interactions. A formula for the calculation of the effective ion-water separation in solution is proposed. Calculated values of the change in Gibbs free energy, enthalpy and entropy of hydration showed good agreement with experiment.